Dwa znaleziska przedmiotów brązowych z III okresu epoki brązu z terenu Polski Środkowej - Nadolska-Horbacz, Krystyna; Horbacz, Tadeusz J. (Acta Universitatis Lodziensis. Folia Archaeologica, 1982)
The authors describe two finds of bronze products from Central Poland (the former Łęczyca district): (votive?) treasure consisting of two brassards with spiral disks discovered at Zimne (Province of Konin), and a dagger from Błonie (Province of Płock); which have been passed to the Museum at Łęczyca. Lack of information about circumstances in which they were discovered hampers among others chronological and cultural analysis of the products. In the light of other finds of this type the brassards from Zimne may be dated back to the first half of the 3rd period of the bronze age and may be linked to the Constantine line. The dagger from Błonie, with a form shaped - in the authors’ opinion - as a result of evolution of similar side-arms met in the 2nd period of the bronze age, represents rather a younger segment of the 3rd period, bronze age which allows to link it to the Central-Poland group of Lusatian culture.